Mycotoxicological Assessment of Broiler Compound Feed: A Multi-Year Analysis of Five Mycotoxins in a Romanian Feed Mill - Dragoș Mihai Lăpușneanu; Silvia-Ioana Petrescu; Cristina-Gabriela Radu-Rusu; Mădălina Matei; Ioan Mircea Pop (Agriculture)
Mycotoxins are secondary metabolites of filamentous fungi that cause massive agricultural losses worldwide and constitute a significant health problem for humans and animals. The aim of this five-year study was to investigate the contamination of compound feed for broiler chickens at all stages (starter, grower and finisher) from a feed mill in Romania with mycotoxins such as total aflatoxins (AFT), deoxynivalenol (DON), fumonisins (FUMs), ochratoxin A (OTA) and zearalenone (ZEN). AFT was detected in 49.3–72.2% of the samples with concentrations ranging from 0.01 to 5.2 µg/kg. DON was detected in 77.6–98.9% of the samples, with maximum concentrations ranging from 330 to 1740 µg/kg. FUM contamination ranged from 42.7% to 87.2%, with maximum levels between 460 and 1400 µg/kg. OTA was present in 44.2–87.9% of the samples, with maximum concentrations reaching 21.4 µg/kg. ZEN was consistently elevated at all feeding stages, being detected in 86.5–97.4% of the samples, with maximum levels of 89.4 µg/kg. Mycotoxin co-occurrence was common in the samples, with the most common combination of four mycotoxins occurring in 38.51% of the samples. Samples were collected from storage bunkers, homogenised and analysed in certified laboratories, with sampling procedures varying according to batch size to ensure representativeness. Investigation of the transfer of mycotoxins into animal products and the combined effects of mycotoxins on animal health, including potential synergistic or antagonistic interactions, is particularly relevant. This study emphasises the essential role of comprehensive and continuous monitoring of mycotoxins in protecting animal health and food safety.